Perancangan Aplikasi Administrasi Santri dan Santriwati TPQ dan TPA AN-NUR Berbasis Web - Annisa Azzahra Firdaus; Exi Purnamasari; Kiki Alfiansyah; Raka Ahmad Saputra; Aries Saifudin (CV. Multi Kreasi Media, 2024)
The lack of a computerized administrative data management system at TPA and TPQ AN-NUR made administrative staff unable to do their job optimally, all students paid their dues and still used books, the researchers found during the research process. The objectives of this research include building work systems, developing information systems, testing and analyzing systems, and implementing more efficient administrative management. A grounded approach (also known as grounded research) is used in this study. With the intention of applying empiricism, constructing concepts, developing theories, and proving hypotheses, this method is based on facts and comparative analysis. Researchers can make it easier for administrative staff after conducting a study and planning of this system at TPA and TPQ AN-NUR. In addition, because everything is done via mobile phones or other devices, it's easier to monitor administration management. No need to pay bills manually with dues books.